The role of metaphors and metonymies in framing the transplantation discourse - Brdar, Mario (Array, 2020)
This article studies figurative uses of metaphors and metonymies utilized to frame the discourse of transplantology. We assume a somewhat wider view of framing than is usually found in the literature and argue that framing effects can be observed on a cline stretching from the private to the institutional pole. We combine this approach with the findings of the prospect theory that distinguishes between gain-framing and loss-framing as two strategic choices in tackling an issue in discourse. The framing tools, as we show in our analysis of authentic materials, in order to be effective need to be adapted to the section of, or the point on, the cline occupied by a particular subtype of discourse. Although the focus in the cognitive linguistic literature is on how conceptual metaphors are employed in framing discourse, we point out that metonymies, interacting with these metaphors, can also play a very important role. The framing tools used in public campaign aimed at winning new organ donors are strategically mostly gain-framed, and as a rule globally based on the gift metaphor. It seems that the metaphorical use of gift as a global choice in institutional contexts is not very efficient since it is too general and vague to make discourse more persuasive at the personal level, as expected in the light of the exemplification theory. This metaphor is more effective when adapted accordingly, as we demonstrated on some campaigns supported by or based on metonymic presentation of various aspects stressing the quality of life after transplantation.